2004
DOI: 10.1074/jbc.m401844200
|View full text |Cite
|
Sign up to set email alerts
|

The Life Span Determinant p66Shc Localizes to Mitochondria Where It Associates with Mitochondrial Heat Shock Protein 70 and Regulates Trans-membrane Potential

Abstract: P66Shc regulates life span in mammals and is a critical component of the apoptotic response to oxidative stress. It functions as a downstream target of the tumor suppressor p53 and is indispensable for the ability of oxidative stress-activated p53 to induce apoptosis. The molecular mechanisms underlying the apoptogenic effect of p66Shc are unknown. Here we report the following three findings. (i) The apoptosome can be properly activated in vitro in the absence of p66Shc only if purified cytochrome c is supplie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

10
240
0
2

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 261 publications
(252 citation statements)
references
References 27 publications
10
240
0
2
Order By: Relevance
“…Hence, while p66Shc triggers the mitochondrial pathway of apoptosis in T cells, the mechanism responsible for mitochondrial recruitment does not appear to involve ROS-dependent PTP opening, at variance with fibroblasts. 13 Trolox treatment abrogated however the enhanced apoptotic response to A23187 of p66Shc-expressing cells (Figure 4), suggesting a role for p66Shc-dependent ROS production in additional apoptotic pathways independent of mitochondria. Support to this hypothesis comes from the functional analysis of the p66Shc S36 mutant (p66SA).…”
mentioning
confidence: 93%
See 3 more Smart Citations
“…Hence, while p66Shc triggers the mitochondrial pathway of apoptosis in T cells, the mechanism responsible for mitochondrial recruitment does not appear to involve ROS-dependent PTP opening, at variance with fibroblasts. 13 Trolox treatment abrogated however the enhanced apoptotic response to A23187 of p66Shc-expressing cells (Figure 4), suggesting a role for p66Shc-dependent ROS production in additional apoptotic pathways independent of mitochondria. Support to this hypothesis comes from the functional analysis of the p66Shc S36 mutant (p66SA).…”
mentioning
confidence: 93%
“…6,10 A fraction of p66Shc localizes to mitochondria as a complex with Hsp70, wherefrom it is released upon UV irradiation. 13 Mitochondrial p66Shc increases ROS production and favors opening of the permeability transition pore (PTP), 13 a high-conductance inner membrane channel involved in the apoptotic response to a number of stimuli. 14 The mechanism whereby p66Shc mediates mitochondrial ROS production has been recently clarified with the demonstration that p66Shc is a redox enzyme able to oxidize cytochrome c and produce H 2 O 2 , causing PTP opening and apoptosis.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, mice lacking p66shc live 30% longer than wild type (Migliaccio et al 1999). Recent work has shown that p66shc is associated with mitochondrial membranes and has been shown to regulate mitochondrial transmembrane potential (Orsini et al 2004). …”
Section: Introductionmentioning
confidence: 99%